Teacher Quality, Instructional Quality and Student Outcomes: Relationships Across Countries, Cohorts and Time - Nilsen, Trude; Gustafsson, Jan-Eric (IEA Research for Education, 2016)
Education; Teaching; Learning and Instruction; Assessment, Testing and Evaluation